Self-ratings of coach and athlete performance-related behaviours in elite Judo - Tanabe, Y.; Cloak, R.; Devonport, T.; Lane, A. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Introduction The purpose of this study is to assess coach and players beliefs in terms of confidence and importance to key performance constructs. A second purpose is to compare and contrast beliefs of confidence and importance by elite vs non-elite coaches and players by male-female competition classification. Methods Participants were 158 Judo athletes and coaches which comprised 42 = elite athletes and 55 non-elite judo athletes, 31 elite coaches and 30 non-elite coaches. Participants completed a 15-item questionnaire (based on the UK Coaching Framework) designed to assess confidence and the importance of Physical Development, Psychological Preparation, Relationships, Skills, and Understanding You. Interview data was collected to conduct a deep-dive into the strengths of beliefs and as a sense-check of questionnaire data. Results Results from 3-way MANOVA results indicated a significant main effects for differences in coach-athlete and gender with no significant elite-non-elite effects. Results showed male coaches consider skills to be the most important category, where male athletes consider physical development the most and relationships to be the least important. Results show male coaches reported high confidence in skills but low confidence in psychological preparation. Male athletes reported high confidence in understanding you and physical development. Female coaches reported high confidence in relationships but low confidence in understanding you. Female athletes reported high confidence in relationships. Qualitative data unpacked the data and revealed differences were more about how male athletes emphasize strength as more of a key quality in performance than females. Qualitative data offers insight into why relationships are important and some of the key contexts were relying on a supportive environment is important. Discussion Judo coaching is a complex involving components such as technical, tactical, psychological, and physical aspects. Coaches play a significant role in the development of athletes, and their behaviours can have a profound impact on athlete outcomes. To produce high performance athletes, understanding the gap between what athletes consider important and what they actually have confidence in compared to what coaches consider important and have confidence in is vital for enabling the latter to change their coaching behaviour accordingly.